2022
DOI: 10.1007/s11104-022-05506-1
|View full text |Cite
|
Sign up to set email alerts
|

Improving the remote estimation of soil organic carbon in complex ecosystems with Sentinel-2 and GIS using Gaussian processes regression

Abstract: Background and aims The quantitative retrieval of soil organic carbon (SOC) storage, particularly for soils with a large potential for carbon sequestration, is of global interest due to its link with the carbon cycle and the mitigation of climate change. However, complex ecosystems with good soil qualities for SOC storage are poorly studied. Methods The interrelation between SOC and various vegetation remote sensing drivers is understood to demonstrate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 104 publications
0
8
0
Order By: Relevance
“…The results of lithologies of the intervened area and lower than the median of the intervened area are in concordance with other studies related to SOC on paramo region in Colombia where a positive asymmetry of 0.97 and kurtosis of 5.18, also estimated SOC values that oscillate in the range of 22 and 338 Mg/ha and medians of up to 180.52 Mg/ha are indicated [48]. Also, studies in the herbaceus páramo ecosystem of Ecuador showed values of SOC between 67-221 in the 0-30 cm soil profile and values of SOC between 32 and 179 Mg/ha in the 30-60 cm profile [49].…”
Section: Discussionmentioning
confidence: 83%
“…The results of lithologies of the intervened area and lower than the median of the intervened area are in concordance with other studies related to SOC on paramo region in Colombia where a positive asymmetry of 0.97 and kurtosis of 5.18, also estimated SOC values that oscillate in the range of 22 and 338 Mg/ha and medians of up to 180.52 Mg/ha are indicated [48]. Also, studies in the herbaceus páramo ecosystem of Ecuador showed values of SOC between 67-221 in the 0-30 cm soil profile and values of SOC between 32 and 179 Mg/ha in the 30-60 cm profile [49].…”
Section: Discussionmentioning
confidence: 83%
“…An interesting property of GPC is the ability to provide band relevance, obtained through automatic relevance determination (ARD) kernels [ 73 ]. The relevance of the features can be demonstrated with a polar plot according to Ayala Izurieta et al [ 74 ]. Hereby, the class-specific relevance for each feature is obtained, with values further away from the center expressing increasing importance.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, summary percentages per class are provided. Right : polar plot of GPC band relevance for the four classes calculated according to the equations described in [ 74 ]. The further away from center, the more important.…”
Section: Figurementioning
confidence: 99%
“…In a study by Emadi et al (2020) using support vector machine (SVM), artificial neural network (ANN), random forest (RF), deep neural network and extreme gradient boost, SOC contents ranged from 0.02% to 11.48% with a mean and standard deviation of 2.19% and 1.27% respectively. Ayala Izurieta et al (2022) revealed that for the 0-30cm depth the SOC values ranged between 3.8-16.4%. As a result, in the 0-30cm depth, the SOC % prediction model had an R 2 of 0.85, RMSE of 1.58% and the SOC (Mgha -1 ) reached, R 2 = 0.79, RMSE = 24.7.…”
Section: Introductionmentioning
confidence: 98%